2017
DOI: 10.1007/s10916-017-0686-7
|View full text |Cite
|
Sign up to set email alerts
|

MyPOD: an EMR-Based Tool that Facilitates Quality Improvement and Maintenance of Certification

Abstract: Maintenance of Certification (MOC) was designed to assess physician competencies including operative case volume and outcomes. This information, if collected consistently and systematically, can be used to facilitate quality improvement. Information automatically extracted from the electronic medical record (EMR) can be used as a prompt to compile these data. We developed an EMR-based program called MyPOD (My Personal Outcomes Data) to track surgical outcomes at our institution. We compared occurrences reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…10 In a single institution retrospective comparison of NSQIP with traditional M&M conference over a 1-year period, NSQIP identified 143 patients with complications as opposed to 58 in M&M. The NSQIP also identified more postoperative deaths and a higher proportion of surgical-site infections and readmissions. Another study that compared NSQIP-Pediatric (NSQIP-P) with surgeon-reported complications at M&M found that M&M captured only 33% of the complications and 83% of the deaths reported in NSQIP-P. 11 Surgical resident reporting also appears to capture pediatric perioperative complications inadequately when compared with the NSQIP-P database. In a 1-year study in a single institution, residents reported 27 complications, as compared to 68 by NSQIP-P.…”
Section: Discussionmentioning
confidence: 99%
“…10 In a single institution retrospective comparison of NSQIP with traditional M&M conference over a 1-year period, NSQIP identified 143 patients with complications as opposed to 58 in M&M. The NSQIP also identified more postoperative deaths and a higher proportion of surgical-site infections and readmissions. Another study that compared NSQIP-Pediatric (NSQIP-P) with surgeon-reported complications at M&M found that M&M captured only 33% of the complications and 83% of the deaths reported in NSQIP-P. 11 Surgical resident reporting also appears to capture pediatric perioperative complications inadequately when compared with the NSQIP-P database. In a 1-year study in a single institution, residents reported 27 complications, as compared to 68 by NSQIP-P.…”
Section: Discussionmentioning
confidence: 99%
“…EHRs are information systems used by healthcare organisations around the world to capture data on patient care. In the context of digital health, the literature has explored EHR technology from many perspectives such as: Investigating the knowledge and skills the health workforce require to utilise EHRs and the data within them [ 16 , 22 ]; Understanding how organisations can efficiently implement EHRs [ 23 ] and their use as signifiers of digital maturity [ 24 ]; Evaluating the use of EHRs to undertake research that is integrated with routine clinical care [ 25 ]; Investigating the effectiveness of the use of EHRs as tools for improving quality of care [ 26 , 27 ] and predicting health trajectories [ 28 ]; Exploring the potential of EHRs to support virtual care and other new healthcare models [ 29 ] and many applications beyond these. …”
Section: Electronic Health Datamentioning
confidence: 99%
“…Investigating the effectiveness of the use of EHRs as tools for improving quality of care [ 26 , 27 ] and predicting health trajectories [ 28 ];…”
Section: Electronic Health Datamentioning
confidence: 99%
“…program launched by the Robert Wood Johnson Foundation, for example, focused on providing transparent and public reporting of provider performance (Christianson, 2016). Similarly, the "MyPOD" program instituted at a children's hospital in Wilmington, DE, relied on electronic medical record data as well as self-reporting by surgeons, to track and target surgeon-specific outcomes (Berman, 2017). Additional programs have focused on assessing patient satisfaction to improve quality of care (Barr, 2006;Harris, 1999;Arnetz, 1996).…”
Section: Policy Implicationsmentioning
confidence: 99%